1990
DOI: 10.1083/jcb.110.2.519
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells secrete a factor that promotes fibroblast contraction of hydrated collagen gels.

Abstract: Abstract. Bovine aortic endothelial cells (BAEC), grown in vitro, are shown to synthesize and secrete factor(s) that stimulate fibroblasts to contract collagen matrices. The amount of contraction-promoting activity in the conditioned media is dependent on conditioning time and the number of cells in the culture. Production of the contraction-promoting activity continues at a high stable level for at least 5 d in serumfree medium but is abolished when the cells are exposed to an inhibitor of protein synthesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
14
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
(23 reference statements)
4
14
0
Order By: Relevance
“…This agrees with the observation that cycloheximide treated fibroblasts, in the presence of serumcontaining medium, contract indistinguishably from untreated fibroblasts (Guidry, 1992;Guidry et al, 1990). Although protein synthesis was arrested, all CH-treated groups had significantly higher collagen content per tissue dry weight.…”
Section: Discussionsupporting
confidence: 90%
“…This agrees with the observation that cycloheximide treated fibroblasts, in the presence of serumcontaining medium, contract indistinguishably from untreated fibroblasts (Guidry, 1992;Guidry et al, 1990). Although protein synthesis was arrested, all CH-treated groups had significantly higher collagen content per tissue dry weight.…”
Section: Discussionsupporting
confidence: 90%
“…More recently, cultured vascular endothelial cells were shown to secret protein factors that promote the contraction of collage lattices made with fibroblasts (Guidry et al, 1990;Chen et al, 1991b). The report by Chen et al (1991b) showed that the endothelial cellderived lattice contraction promoting factor($ is probably distinct from all known fibroblast mitogens and…”
mentioning
confidence: 96%
“…More recently, cultured vascular endothelial cells were shown to secret protein factors that promote the contraction of collage lattices made with fibroblasts (Guidry et al, 1990;Chen et al, 1991b). The report by Chen et al (1991b) showed that the endothelial cellderived lattice contraction promoting factor($ is probably distinct from all known fibroblast mitogens and In this report, we show that contraction of collagen lattices made with fibroblasts in 1% FBS is inhibited by intracellular CAMP-raising drugs and that the inhibition is attenuated by several polypeptide growth factors including aFGF, TGF-P, and insulin.…”
mentioning
confidence: 99%
“…Antibodies against the integrin receptor subunits alpha 2 beta 1 inhibit cell contraction of collagen gels, indicating that the contractile forces are transmitted to collagen matrices through integrin receptors (Gullberg et al, 1990;Klein et al, 1991;Schiro et al, 1991). A number of studies have confirmed that fibroblast contraction of collagen is stimulated by exogenous factors, the most common source being serum (Bell et al, 1979; 0 1993 WILEY-LISS, INC Steinberg et al, 1980;Guidry and Grinnell, 1985;Guidry et al, 1990). The contraction-stimulating activity in serum can be attributed, at least in part, to the well-established effects of transforming growth factor beta (TGFP) (Montesano and Orci, 1988;Fukamizo and Grinnell, 1990;Raymond and Thompson, 1990) and platelet-derived growth factor (PDGF) (Anderson et al, 1990;Clark et al, 1989;Gullberg et al, 1990), which are released from platelets during blood coagulation.…”
mentioning
confidence: 99%
“…The contraction-stimulating activity in serum can be attributed, at least in part, to the well-established effects of transforming growth factor beta (TGFP) (Montesano and Orci, 1988;Fukamizo and Grinnell, 1990;Raymond and Thompson, 1990) and platelet-derived growth factor (PDGF) (Anderson et al, 1990;Clark et al, 1989;Gullberg et al, 1990), which are released from platelets during blood coagulation. Other sources of contraction-stimulating activity include the secretory products of endothelial cells (Guidry et al, 19901, retinal pigmented epithelial cells (Guidry et al, 19921, and several transformed cell types (Guidry et al, 1990). Studies of cell-conditioned medium revealed that the endothelins (Yanagisawa et al, 19881, a family of small bioactive peptides, are also potent promoters of fibroblast contraction (Guidry and Hook, 1991).…”
mentioning
confidence: 99%